1987
DOI: 10.1042/bj2420695
|View full text |Cite
|
Sign up to set email alerts
|

Properties and distribution of the protein inhibitor (Mr 17,000) of protein kinase C

Abstract: Ca2+-dependent hydrophobic-interaction chromatography is a powerful tool for the identification and isolation of a variety of Ca2+-binding proteins which expose a hydrophobic site(s) in the presence of Ca2+ [Gopalakrishna & Anderson (1982) Biochem. Biophys. Res. Commun. 104, 830-836; Walsh, Valentine, Ngai, Carruthers & Hollenberg (1984) Biochem. J. 224, 117-127; McDonald & Walsh (1985) Biochem. J. 232, 559-567]. Using this approach, we isolated two potent and specific protein inhibitors of protein kinase C, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 47 publications
(41 reference statements)
2
33
0
Order By: Relevance
“…2L). These data are in line with previous reports on the expression levels of Hint protein in the brain, stomach, and kidney (13,20). Hint expression in the adult testis continued to be most prominent in the germ cells, where the highest expression was found in the pachytene spermatocytes (unpublished data).…”
Section: Resultssupporting
confidence: 92%
“…2L). These data are in line with previous reports on the expression levels of Hint protein in the brain, stomach, and kidney (13,20). Hint expression in the adult testis continued to be most prominent in the germ cells, where the highest expression was found in the pachytene spermatocytes (unpublished data).…”
Section: Resultssupporting
confidence: 92%
“…ttLeast squares fitted rms deviations (rmsd) from noncrystallographic symmetry (ncs) between protomers in the asymmetric unit. 18-23) and B (residues 71-86) and ,B elements numbered 1 (residues 31-35), 2 (residues 38-42), 3 (residues 50-56), 4 (residues 94-100), and 5 (residues 111-118). These figures were generated using SETOR (24 Mycobacterium laprae (U15187), and Saccharomyces cerevisiae (4).…”
Section: Resultsmentioning
confidence: 99%
“…This antibody also detected a protein of the expected molecular weight in primary human skin fibroblasts, mouse NIH 3T3 fibroblasts, rat 6 fibroblasts, K22 rat liver epithelial cells, bovine aortic endothelial cells, HC11 mouse mammary epithelial cells, rat intestinal epithelial cells, IEC18, and several other cell lines (data not shown). Other studies (2,5) have shown that PKCI-1 is present in a wide variety of tissues, indicating that it is expressed across a broad range of species and tissue.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Based on its characteristic actions, it is presumed that CPB I may be involved in cellular signal transduction through regulation of Ca2+ concentration, arachidonic acid cascade, and inositol phospholipid turnover. To date, several potent synthetic and naturally occurring inhibitors of PKC have been described (Hidaka and Hagiwara 1987), but there are few reports on the endogenous inhibitor of the PKC activity (McDonald et al 1987). Since CPB I is a Ca2+-and phospholipid-dependent protein like PKC, we are interested in whether CPB I affects the PKC activity.…”
mentioning
confidence: 99%